A QUASI-INTERPOLATION SPLINE FOR CAUCHY INTEGRAL EQUATIONS VIA REGULARIZATION - Mennouni, A (Rendiconti del Seminario Matematico della Università di Padova, 2018)
In this paper, we present some our ongoing researches related to a collocation method based on a double projection scheme via regularization procedure, to numerically solve Cauchy integral equations of the second kind. For the collocation approach, we use spline quasi-interpolating projectors of degree $d$. We prove the existence of the solution for a double projection scheme. Moreover, we give new error bounds.